About an Intracranial Aneurysm Rupture During Delivery - Assoumane, Ibrahim; Houari, Loucif; Morsli, Abdelhalim (Indian Journal of Neurosurgery, 2020)
The rupture of an intracranial aneurysm is rare during pregnancy and exceptional during delivery. When it occurs, the prognosis of two lives is engaged. We are reporting a case of a 41-year-old patient presenting with a subarachnoid hemorrhage during labor. After extraction of healthy baby through cesarian section, radiological investigations permitted to diagnose a ruptured right carotid-ophthalmic aneurysm. The patient benefited from a selective aneurysm’s exclusion by occlusion using Guglielmi detachable coils through an endovascular approach using catheterization. The immediate outcome was favorable.
Keywords: aneurysm; pregnancy; delivery; endovascular